Narratives of Resilience: Exploring Student Stories During Remote Learning in the COVID-19 Pandemic - Catherine Li; Rahmat Hidayat; Kumudu Wijerathna; Alma Yulianti (Yayasan Adra Karima Hubbi, 2025)
Background. The COVID-19 pandemic forced an abrupt transition from face-to-face instruction to remote learning, exposing students worldwide to significant academic, technological, and psychosocial challenges. Purpose. This study aimed to explore students’ lived experiences of resilience during remote learning by examining their narratives of adaptation, coping strategies, and personal development in online educational contexts. Method. A qualitative research design employing narrative inquiry was used. Data were collected from 50 secondary and tertiary students across diverse educational settings through in-depth narrative accounts. Results. The findings revealed that students demonstrated resilience through proactive time management, creative engagement with digital platforms, peer collaboration, and positive cognitive reframing of challenges. Participants reported enhanced self-directed learning skills, increased autonomy, and improved emotional regulation as outcomes of prolonged remote learning. Conclusion. The study concludes that resilience plays a vital role in sustaining student engagement and well-being in remote learning environments.